The body or the soul? : religion and culture in a Quebec parish, St-Joseph-de-Beauce, 1736-1901 - Abbott, Frank Albert, 1950- (McGill-Queen's studies in the history of religion, 2016)
How a Quebec community fashioned a resilient balance between freedom and faith out of their culture and their Catholicism.